معنى الصيام من خلال سورة البقرة: دراسة تحليلية - Mubarak Ibrahim At-Tajany (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Acts of worship have specific times and seasons, some of which are more virtuous than others. A believer always seeks these blessed times in pursuit of increased rewards and elevated ranks. The holy month of Ramadan is one such virtuous period, honored by Allah with numerous merits. The researcher aimed to highlight these merits through an analytical study of the verses on fasting in Surah Al-Baqarah, with the objective of encouraging Muslims to make the most of this sacred time through acts of worship. The study yielded significant findings, including that fasting is a means to attain piety, clearly demonstrates Allah’s mercy and ease upon this Ummah, and serves as a lesson in patience. Additionally, it affirms that a person can change negative habits and corrupt behaviors. Fasting also brings a person closer to Allah, making their supplications more likely to be accepted. Moreover, it is a season for caring for the poor and needy, bringing them joy, and purifying the soul through fasting, prayer, and spiritual retreat. May Allah grant benefit through this effort and accept it sincerely for His sake.